Oxygen delivered by a high flow concentrator for the treatment of medication-overuse headache - Jerome Mawet; Dominique Valade; Marie Vigan; Cedric Laouenan; Caroline Roos (SAGE Publishing, 2018)
Treatment of medication-overuse headache (MOH) relies on detoxification, during which patients face rebound headache without alternative to painkiller. As oxygen has been proven effective for cluster and other headache subtypes, we sought to evaluate use of normobaric oxygen delivered by a high flow concentrator (HFC) in patients suffering MOH. For this purpose, twenty patients with MOH were included in this prospective monocentric open-labeled feasibility study. All patients received standard care with detoxification in addition to HFC delivering normobaric oxygen at 9 l/min, used to their discretion to treat rebound headache. Primary endpoint was acceptance of HFC and secondary endpoints evaluated its efficacy. Four patients were lost of follow-up after inclusion, one was excluded. HFC was accepted by 14/15 (93.3%). At M6 of follow-up, 15/15 (100%) reverted to episodic headache. In conclusion, normobaric oxygen delivered by HFC appears to be safe, feasible, and probably efficient to help patient with MOH who undergo withdrawal therapy. A larger double-blind, sham-controlled prospective study is needed. Trial registration : Clinical trials: NCT02302027.